High temperature absorption properties of SiOC ceramic matrix composite reinforced by continuous microwave- absorbing SiC fibers - SHI Qiaoying; LI Jingdan; GAN Nianyu; LI Siwei (Cailiao gongcheng)
The SiC-BN/SiOC ceramic matrix composites are prepared through the precursor infiltration pyrolysis（PIP） process， using wave-absorbing SiC fibers with in-situ BN coatings as reinforcements and SiOC ceramic as the matrix. After 7 PIP preparation cycles， the composite achieves densification with density of 2.05 g/cm³ and porosity of 4.28%. The dielectric constants are tested with vector network analyzer. Using transmission line theory， the microwave-absorbing properties of the composites from room temperature to 800 ℃ at 8.2-18 GHz are optimized. The results show that the dielectric constants of the SiC-BN/SiOC composites exhibits significant frequency dispersion effects， leading to broadband microwave-absorbing properties. When the thickness of the composites is 2.1 mm， the maximum bandwidth of the reflection loss better than -10 dB in the X band and the Ku band is 5.7 GHz. As the ambient temperature increases， the real and imaginary parts of the complex permittivity of the composites both increase. For reflection loss better than -5 dB in a wide bandwidth， the optimum thicknesses decrease from 2.3 mm （200 ℃） to 1.1 mm （800 ℃）.